Differences in the Characteristics of Ischemic and Haemorrhage Stroke Patients with Mechanical Phlebitis - Yeni Siswanti; Ika Yuni Widyawati; Candra Panji Asmoro (Universitas Airlangga, 2021)
Introduction: One of the complications of stroke patients receiving intravenous therapy is mechanical phlebitis. The purpose of this study was to analyze the differences characteristic of stroke patients who experienced mechanical phlebitisMethods: This study was used a comparative descriptive method with a documentation study design. The subjects of this study were stroke patients who experienced mechanical phlebitis from January 2018 until September 2020. The sampling method used total sampling with 92 samples. Data analysis using Chi-squared test.Results: Gender (p = 0.020) had a significant difference with the incidence of mechanical phlebitis in stroke patients. Characteristics of age (p=0.511), history of hypertension (p=0.058), diabetes mellitus (p=0.503), pneumonia (p=0.164), and stroke (p= 0.160) did not have a significant difference with the incidence of mechanical phlebitis in stroke patients.Conclusion: There are differences in gender characteristics in stroke patients who experience mechanical phlebitis.